Respon Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) terhadap Beberapa Dosis Pupuk Kandang Kotoran Itik pada Tanah Rawa Lebak - Nur Hafizah; Fikriah Fikriah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2011)
Lettuce plants in the process of growth and development require additional nutrients by repair Techniques for cultivation and repair of organic or inorganic fertilizers. Organic fertilizers are also called natural fertilizers because all or most of them come from natural fertilizers. This study aims to (i) find out the effect of giving dung manure to the growth and yield of lettuce on swampy soil, (ii) get the best dose from the administration of duck manure to the growth and yield of lettuce on swampy swamp soil. This research was conducted in Hambuku Tengah Village, Sungai Pandan District from April to June 2010. Using a Completely Randomized Design (CRD). The factors studied were 9 doses of duck manure fertilizer dosage with 9 treatments, there are b0 = 0 t.ha-1; b1 = 2,5 t.ha-1; b2 = 5,0 t.ha-1; b3 = 7,5 t.ha-1; b4 = 10 t.ha-1 ; b5 = 12,5 t.ha-1; b6 = 15,0 t.ha-1; b7 = 17,5 t.ha-1; b8 = 20,0 t.ha-1 with 3 replications, thus there were 27 experimental units. The observed variables were plant height and number of leaves aged 14, 21, 28 and 35 days after planting (DAP) and leaf wet weight at harvest. From the results of the study there was a response of tall mustard plants aged 28 HST and wet weight of mustard plants but there was no response to the height of mustard plants aged 14, 21 and 35 HST on the administration of duck manure, with the best dose was treatment b4 (10 t.ha -1)